ANTIBACTERIAL ACTIVITY TEST OF N-HEXANE AND ETHANOL EXTRACT OF MELINJO PEEL (GNETUM GNEMON L.) AGAINST SHIGELLA DYSENTERIAE AND BACILLUS CEREUS - Anas Gilang Pratama; Saiful Bahri; Herdini (Journal of Research in Pharmacy and Pharmaceutical Sciences, 2023)
Melinjo peel (Gnetum gnemon L.) contains secondary metabolites with antibacterial characteristics such as alkaloids, flavonoids, saponins, tannins, and steroids. This study aims to determine the antibacterial activity of 96% ethanol and n-hexane extract of melinjo peel resulting from the multilevel maceration against Shigella dysenteriae and Bacillus cereus bacteria. This research is an experimental study to test the antibacterial activity of melinjo peel extract as measured by the Diameter of Inhibition Zone (DIZ) and Minimum Inhibitory Concentration (MIC) at concentrations of 12.5%, 25%, and 50%. The results found that the extract resulted from maceration with 96% ethanol solvent as much as 70.95 g with a yield of 14.19% and n-hexane solvent as much as 7.07 g with a yield of 1.41%. The 96% ethanol extract of melinjo peel gave the highest DIZ at a concentration of 50% against Bacillus cereus compared to Shigella dysenteriae. In contrast, the DIZ of n-hexane extract of melinjo peel had no inhibitory power against both of bacteria in all concentrations. MIC of 96% ethanol extract of melinjo peel extract against Shigella dysenteriae and Bacillus cereus at concentrations of 50% and 25%, respectively, whereas n-hexane extract melinjo peel had no MIC value against both bacteria.